(untitled) (International Journal of Engineering and Computer Science, 2017)
Filters play an important role in noise removal. There are many different types of filter architecture that have been proposed. Reconfigurable architectures of FIR filter are used in application like software defined radio (SDR) which support multistand communication and also in medical application. In this designed work Reconfigurable Finite Impulse Response (FIR) filter is designed for Electro Encephalo-Gram (EEG) application. The filter is in transpose form which support pipelining and multiple constant multiplications (MCM). Area and delay is calculated on FPGA using XILINX 14.2 software and filtering of EEG signal using MATLAB 2013a. The design is less complex utilizing less area and delay. The overall delay for block size 8 was 12.17ns and frequency 167.57 MHz